Prevalence of disrespect and abuse and its determinants during delivery in rural Uttar Pradesh India - Yadav, Akhilesh; Singh, T. B.; Sachan, Shikha (International Journal Of Community Medicine And Public Health, 2022)
Background: Disrespect and abuse treatment during childbirth in health facilities is a burning issue all over the world and emerged as a common problem in maternal health care. It is contributing to untold suffering and discouraging women from seeking care in health facilities. Women experiencing disrespect, abusive, or abandonment during childbirth is an international agenda. This study aims to estimate the prevalence of disrespect and abuse (D and VA) during delivery and identifies the associated factors. Methods: A community-based cross-sectional survey was conducted in the Balarampur district of Uttar Pradesh, India. The study included 364 women who underwent facility-based childbirth before six months of the survey. A multistage cluster sampling was used to select the potential participants of the study. Results: the findings of the study show Utmost every woman (98.5%) experienced any kind of disrespect or abuse during institutional delivery. However, 92% of women experienced non-consent care in which women were neither informed nor their verbal or written consent was taken before any medical procedures in the labor room. Disrespect and abuse during labor and delivery were significantly associated with Age group, religion, level of education, age at marriage, place of delivery, no. of ANC visit. Conclusions: Every woman has the right to receive kind and respectful maternity care, and mistreatment during maternal care services remains hindrance to achieving safe motherhood and child care.